2007
DOI: 10.1080/17429140701422496
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of some synthetic monoethanolamine salts ofpara-substituted benzoic acids and corresponding benzoic acids on cucumber seed germination

Abstract: Benzoates and particularly, benzoic acids are known biologically for their effects in the regulation of seed germination. A series of monoethanolamine salts of para -substituted benzoic acids (MEASPBAs), the corresponding acids (BAs) and monoethanolamine (MEA) were tested at different concentrations, on Cucumis sativus L. germination in order to assess their biological activity. The correlation between the effects of different substituents of these salts and the corresponding acids with germination rate, root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…The pH also has an important role in determining the toxicity of the compound, with the toxicities decreasing as the pH increases (Zhao et al 1996(Zhao et al , 1998. Regarding the phytotoxicity of halogenated benzoic compounds, the tests on C. sativus (Cris¸an et al 2007) and this study show that similar conclusions can be drawn from the data: the halogenated MEASPBAs present a more inhibitory effect in comparison with the corresponding BAs compared to the controls. The data, once again, indicate that both ionized and unionized forms of a chemical can contribute to toxicity (Barron 1990;Zhao et al 1998).…”
supporting
confidence: 77%
See 3 more Smart Citations
“…The pH also has an important role in determining the toxicity of the compound, with the toxicities decreasing as the pH increases (Zhao et al 1996(Zhao et al , 1998. Regarding the phytotoxicity of halogenated benzoic compounds, the tests on C. sativus (Cris¸an et al 2007) and this study show that similar conclusions can be drawn from the data: the halogenated MEASPBAs present a more inhibitory effect in comparison with the corresponding BAs compared to the controls. The data, once again, indicate that both ionized and unionized forms of a chemical can contribute to toxicity (Barron 1990;Zhao et al 1998).…”
supporting
confidence: 77%
“…Pure crystals were washed with acetone and diethylether and then dried for several hours under vacuum. The physicochemical properties of MEASPBAs were previously reported by Cris¸an et al (2007).…”
Section: Measpba Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, BAs can alter membrane permeability by solubilizing into cellular membranes and/or adsorbing to membranes to produce either a negative surface potential or an increase in the anionic field strength of the membrane (Heipieper et al 1991, Baziramakenga et al 1995, Barron et al 1996. It has been demonstrated that the number and position of BA hydroxy and methoxy ring substituents play an important role in their inhibitory activity towards ion uptake (Yu & Matsui 1997, Yu et al 2003, Ye et al 2004) and plant growth (Crisan et al 2007). …”
Section: Introductionmentioning
confidence: 99%